Acid deposition in Asia: Emissions, deposition, and ecosystem effects. (December 2016) - Duan, Lei; Yu, Qian; Zhang, Qiang; Wang, Zifa; Pan, Yuepeng; Larssen, Thorjørn; Tang, Jie; Mulder, Jan
Abstract: We review and synthesize the current state of knowledge regarding acid deposition and its environmental effects across Asia. The extent and magnitude of acid deposition in Asia became apparent only about one decade after this issue was well described in Europe and North America. In addition to the temperate zone, much of eastern and southern Asia is situated in the tropics and subtropics, climate zones hitherto little studied with respect to the effects of high loads of acid deposition. Surface waters across Asia are generally not sensitive to the effects of acid deposition, whereas soils in some regions are sensitive to acidification due to low mineral weathering. However, soil acidification was largely neutralized by such processes as base cation deposition, nitrate (NO3 − ) denitrification, and sulfate (SO4 2− ) adsorption. Accompanying the decrease in S deposition in recent years, N deposition is of increasing concern in Asia. The acidifying effect of N deposition may be more important than S deposition in well drained tropical/subtropical soils due to high SO4 2− adsorption. The risk of regional soil acidification is a major threat in Eastern Asia, indicated by critical load exceedance in large areas. Highlights: Here review more recent studies on acid deposition in Asia, especially in Eastern Asia. Surface waters are generally not sensitive to acid deposition in comparison with soils. Soil acidification is not very serious because of base cation deposition, N denitrification, and SO4 2− sorption.